(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Cigarette smoke is one of the exogenous free radicals that can enter the blood circulation so that it candisrupt all body cells and tissues, including the reproductive organs. The anthocyanin in purple sweetpotato is one of the bioactive that can counter free radicals. This study was conducted to prove the effectof anthocyanin in purple sweet potato from Gunung Kawi cultivar on follicle-stimulating hormone (FSH),and folliculogenesis levels on Wistar rats (Rattus norvegicus) exposed to cigarette smoke. This study wasan experimental study with Randomized Post Test Only Control Group Design, using 30 female Wistar ratsaged 1-2 months weighing 150-200g. The rats were divided into three groups of where they were exposedto cigarette smoke and administered with anthocyanin (each group with the doses of 20, 40 and 80 mg/kgbw/day). One positive control group was exposed to cigarette smoke without being administered withanthocyanin for 56 days, and one more group served as a negative control. The FSH levels in the serum weremeasured by employing the ELISA method, and the folliculogenesis (follicle amount and number of ovaryfollicular granulosa cells) was measured from histopathological slides with Haematoxylin-Eosin staining.The results indicated that anthocyanin in purple sweet potato significantly increased the FSH levels, thefollicle amount and the number of primary follicular granulosa cell, secondary, and Graafian on femaleWistar rat ovaries exposed to cigarette smoke with a p-value of less than 0.05. To ensure the anthocyanindose that had maximum effect, more research is required with more dose variations and chronic toxicity testsfor the safety of the anthocyanin in purple sweet potato of Gunung Kawi cultivar.